Consider 56 * 66 * 1
56 * (66 * 1)
56*(66)
(50 + 6) (60 + 6)
50(60 + 6) + 6(60 + 6)
(50*60) + (50*6) + (6*60) + (6*6)
3000 + 300 + 360 + 36
3696
Therefore, 56*66*1 = 3696
Source: www.icoachmath.com
If the equation looks like this: (10x-3)(2x-5), then simplified it is 20x2-56x+15 If the equation looks like this: 10x-3(2x-5), then simplified it is 4x+15
-56x-4
-1
7X^2 -56X + 112 = 0 divide through by 7 X^2 - 8X + 16 = 0 factor (X-4)(X-4) X = 4
9/1 = 9.
Problem: -4-56x= 20. -56x=20+4. -56x/56=24/56. Answer: approx. .43
Model VWB19069A Serial 66X 11013
If you mean: d = 56x+72y So if: 8 = 56x+72y Then: x = 1/14 and y = 1/18 Check: (56*1/14)+(72*1/18) = 8
16x2 - 56x + 49 = (4x - 7)2
The value of x in the equation 49x2 plus 56x plus 16 is -2.04.
4x+6=6x-12
49x2 - 56x + 16 = (7x - 4)2 so yes, it can be a perfect square.
-4x2 - 32x + x + 8 = 8x2 - 56x : simplify and group the various terms-32x + 56x + x + 8 = 8x2 + 4x225x + 8 = 12x2 : Now present this as a standard quadratic equation.12x2 - 25x - 8 = 0 : Solving for the roots of a quadratic equation gives :-x = [25 ± √(252 + 4x12x8)] ÷ 2x12 = [25 ± √1009] ÷ 24 = [25 ± 31.765] ÷ 24x = 56.765/24 = 2.365 and x = -6.765/24 = -0.282x = 2.365 and -0.282
It simplify to 1
If the equation looks like this: (10x-3)(2x-5), then simplified it is 20x2-56x+15 If the equation looks like this: 10x-3(2x-5), then simplified it is 4x+15
(3x+12)(5x+2)
8x